2016
DOI: 10.1042/bj20150805
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial and plant HAD enzymes catalyse a missing phosphatase step in thiamin diphosphate biosynthesis

Abstract: The penultimate step of thiamin diphosphate (ThDP) synthesis in plants and many bacteria is dephosphorylation of thiamin monophosphate (ThMP). Non-specific phosphatases have been thought to mediate this step and no genes encoding specific ThMP phosphatases (ThMPases) are known. Comparative genomic analysis uncovered bacterial haloacid dehalogenase (HAD) phosphatase family genes (from subfamilies IA and IB) that cluster on the chromosome with, or are fused to, thiamin synthesis genes and are thus candidates for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
35
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 44 publications
3
35
1
Order By: Relevance
“…The same study also identified a homologous enzyme in Arabidopsis thaliana (At4g29530) that showed a similarly strong preference for ThMP. However, knocking out the At4g29530 gene did not affect growth or the levels of thiamin, ThMP, or ThDP, indicating that At4g29530 is not the major Arabidopsis ThMP phosphatase (Hasnain et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…The same study also identified a homologous enzyme in Arabidopsis thaliana (At4g29530) that showed a similarly strong preference for ThMP. However, knocking out the At4g29530 gene did not affect growth or the levels of thiamin, ThMP, or ThDP, indicating that At4g29530 is not the major Arabidopsis ThMP phosphatase (Hasnain et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Our previous work raised the possibility that the At4g29530 HAD enzyme makes a minor contribution to total ThMP phosphatase activity in vivo (Hasnain et al, 2016). We therefore checked whether At4g29530 activity is a source of the residual ThMP phosphatase in th2-1 mutant plants by crossing the At4g29530 knockout (Hasnain et al, 2016) with th2-1 plants to obtain the double homozygous mutant.…”
Section: Complementation and Insertional Mutation Confirm At5g32470 Amentioning
confidence: 99%
See 3 more Smart Citations